New ways to cope with depression—study protocol for a randomized controlled mixed methods trial of bouldering psychotherapy (BPT) and mental model therapy (MMT) - Kind, Leona; Luttenberger, Katharina; Leßmann, Vivien; Dorscht, Lisa; Mühle, Christiane; Müller, Christian P.; Siegmann, Eva-Maria; Schneider, Sophia; Kornhuber, Johannes (Trials, 2023)
Background: Due to the growing gap between the demand and supply of therapeutic services for people suffering from depression, with this study, we are investigating the effectiveness and factors of influence of new approaches in group treatments for depression. Two previous studies have already identified bouldering psychotherapy (BPT) as an effective option. It combines psychotherapeutic interventions with action- and body-oriented bouldering exercises. Mental model therapy (MMT) is a new cognitive-behavioral approach for treating depression. It focuses on identifying cognitive distortions, biases in decision making, and false assumptions and aims to correct and replace them with useful mental models. We aim to investigate the effectiveness of the interventions compared with a control group (CG) and to assess the factors of influence in a mixed methods approach. Methods: The study is being conducted as a randomized controlled intervention trial. Adult participants with unipolar depression are being randomized into three groups (BPT, MMT, or CG), and the first two groups are undergoing a 10-week treatment phase. CG follows their individual standard treatment as usual. A priori power analysis revealed that about 120 people should be included to capture a moderate effect. The primary outcome of the study is depression rated with the Montgomery and Asberg Depression Rating Scale (MADRS) before (t0), directly after (t1), and 12 months after the intervention phase (t2). Data are being collected via questionnaires, computer-assisted video interviews, and physical examinations. The primary hypotheses will be statistically analyzed by mixed model ANOVAs to compare the three groups over time. For secondary outcomes, further multivariate methods (e.g., mixed model ANOVAs and regression analyses) will be conducted. Qualitative data will be evaluated on the basis of the qualitative thematic analysis. Discussion: This study is investigating psychological and physical effects of BPT and MMT and its factors of influence on outpatients suffering from depression compared with a CG in a highly naturalistic design. The study could therefore provide insight into the modes of action of group therapy for depression and help to establish new short-term group treatments. Methodological limitations of the study might be the clinical heterogeneity of the sample and confounding effects due to simultaneous individual psychotherapy. Trial registration: ISRCTN, ISRCTN12347878. Registered 28 March 2022, https://www.isrctn.com/ISRCTN12347878 .
CRIS-Team Scopus Importer:2023-09-29
Keywords: Biomarkers; Bouldering; Depression; Exercise; Factors of influence; Mental models; Osteocalcin; Psychotherapy; Rock climbing; Sports